Pelatihan Desain Branding Untuk Membentuk Identitas Visual Bagi Siswa Sekolah Janji Baik - Putri, I Gusti Ayu Agung Aristi; Yulianto, Arief; Khaer , Ananda Fiky Dibanu (PUAN INDONESIA, 2024)
Janji Baik School is a free digital-based school in South Tangerang, that provides education for economically disadvantaged children. One issue faced by students is the lack of hard and soft skills. To address this, the Visual Communication Design Program of Media Nusantara Citra University organized a branding design training program for Janji Baik School students to enhance their knowledge and skills.This community service activity used a qualitative approach with participatory methods. Implementation stages included preparing training materials, presenting branding design concepts, practical use of the Canva application, and creating group-based branding design projects. Evaluation was done through assessment of student work, monitoring of implementation, and documentation of results.The training results showed improved student understanding and skills in branding design. Students were able to create creative visual identities in line with design principles. The participatory approach and direct guidance from facilitators increased interaction and active student involvement. With these design skills, students can create strong visual identities and enhance their competitiveness in the business world.